DRUM BRAKE CALCULATION ON HONDA TIGER REVO 200 CC - Bogie Reza Saputra; Kardiman .; Najmudin Fauji (Universitas Muhammadiyah Semarang, 2022)
The brake system is one of the components of the engine elements on the vehicle that can support the comfort and safety factor in driving. Brakes function to slow down or stop the movement of the wheels by means of friction. The kinetic energy lost from a moving object is usually converted into heat due to friction. The purpose of this report is to find out the functions, working principles and calculations as well as to know the things that must be considered in planning the drum brake. The method used to make this report is from direct observation of the object, literature study and guidance from the supervisor. From the drum brake specifications that have been described, we can find out the calculation steps needed to find the normal force on the rear wheels, the permissible frictional force, and the maximum use of the brakes. After several calculation steps, the torque on the brakes is 41.82kg.m, the gripping force on the drum brakes is 30.1 kg, the frictional force on the drum brakes is 14.45 kg, the braking capacity of the drum brakes is 2.023 kg. m, the number of braking contacts is 16856contacts. In one month it is assumed that 2500 times the braking contact will be obtained, so that the life of the drum brake pads is 6 months. The canvas can last longer or it can run out quickly depending on the user's usage and further research is needed if you want to get more accurate results because the different types of material and the difference in braking time will affect the lifespan of the brake pads.